Relationship between smartphone addiction and eating disorders and lifestyle among Chinese college students - Wang, Jun; Hao, Qing-Hong; Peng, Wei; Tu, Yang; Zhang, Lan; Zhu, Tian-Min (Frontiers in Public Health, 2023)
Purpose: Smartphone addiction has been widely concerned by the society and parents because of its high incidence as well as serious negative effects. This study aims to determine the association between smartphone addiction and eating disorders and lifestyle among college students. Methods: A descriptive, cross‐sectional study consisted of 1112 college students involved several universities in Chengdu, China. The data were collected by using the Chinese version of Mobile Phone Addiction Index (MPAI), the Eating Attitudes Test-26 (EAT-26). In addition, the information on socio-demography, lifestyle and smartphone use was obtained through a self-administered questionnaire. Results: The prevalence of smartphone addiction was 22.6% among the students in the study. 10.4% of the participants were at risk for eating disorders. Female students had higher MPAI scores and EAT-26 scores than male students (p<0.001). The proportion of male students with the risk of eating disorder were significantly higher than that of female students (p<0.05). The total EAT-26 scores of students with smartphone addiction were higher than that of others (p<0.001).The correlation analysis indicated that the MPAI scores was significantly positively correlated with EAT-26 scores, depression and anxiety, difficulty in falling asleep at night and the frequency of fast-food as well as carbonated soft drink (p<0.01). In addition, the MPAI scores was significantly negatively correlated with the skip breakfast, the frequency of physical activity (p<0.05). Conclusion: Smartphone addiction is significantly associated with eating disorders, eating habits, as well as lifestyle. The influence of dietary habits and lifestyle needs to be considered in the prevention and development of intervention for smartphone addiction among college students.